The Sentencing Effectivity on the Criminal Offense of Corruption Through the Perspective of Indonesian State Administrative Law: A Review - Handaru Arya Ahmad Musyaffar; Radhitya Pratama (Fakultas Hukum Universitas Islam Al-Azhar Mataram, 2023)
Corruption is an act of abusing the legally given power by an entitled public officer or a legal entity, at the length of acting outside of their official capacities that are within the legal duty, with the intention of taking advantage of the policy’s loopholes that are mainly regulating the act of conduct. Presently, corruption can be described as an act that is done by the person per se, not per the Actions solely, in which every action that ‘Actions’ outside of its formal domain of conduct, should be considered as corruption. Many scholars condemn the act of corruption as a discourse of discrepancy throughout the form of an interpersonal, social, moral, and legal order from its own.